Dracaena rosulata (Asparagaceae)—a new species from D.R. Congo - Mwachala, Geoffrey; Fischer, Eberhard (Phytotaxa, 2013)
Dracaena Linnaeus (1767: 229) comprises about 46 species in Africa (Bos 1984, Mwachala 2005). The genus is closely related to Sansevieria Thunberg (1794: 65) and both genera form the Dracaenoid clade within Convallariaceae (APG 1998). Later Rudall et al. (2000) pointed out that the name Ruscaceae has priority over Convallariaceae. According to APG III (2009) Ruscaceae are considered a synonym of Asparagaceae. While preparing a revision of Dracaena for Tropical Africa and the treatment for "Flore d’Afrique Centrale" several unidentified specimens came to light which proved to represent new species. Two of them have been described recently (Mwachala et al. 2007, Mwachala & Cheek 2012). One new species is described in the present paper.